Parameterization Modeling of Drop Arm Thickened Tooth Segment of Steering Gear based on CATIA - Cheng Chen; Jin Gu; Shenghuai Wang; Kang Chen (Jixie chuandong)
The modified gear involute equation under Cartesian coordinates system is established and the theory foundation is provided for parameterization modeling of modified gear. The character of drop arm thickened-tooth segment of steering gear is analyzed. The modified gear involute parameterization equation is established based on the CATIA and the method of parameterization three-dimensional modeling of the thickened tooth segment is detailed. Then the space analysis and motion simulation are implemented for the Digital Mock-Up of steering gear. This method is high modeling accuracy, it is very convenient and the accurate thickened-tooth segment models can be obtained quickly by changing the relevant parameters, which provide the basis for digital assembly and NC machining.